(3efGSc GdMLs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd HjJg ddESdGe YdeG (B... (3hbO QJHJg Ydi ebOeI hHGHjf hNGJeI(B. (3GdebOeI aj CehQ jfHZj JbOjegG hGdJfHjg YdjgG efgG Cfg jfHZj def YRe Ydi GdMLs
(3BNQgG (B:s
(3BNQgG(B: (3hcPdc jRhQ GdCFeI eG GSJWGY hdjMaX faSg ajgG ef GdeBKe hGdeXGde haj GdUObI ajgG Ydi GdeMGhjL ef GdehGdjf KhGH LRjd hNUhUG Ydi PQjI QShd Gddg Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis